Synthesis and characterization of polyarylacetylene for use in the monolithic vitreous carbon processing - Oishi, Silvia Sizuka [UNESP]; Botelho, Edson Cocchieri [UNESP]; Luscombe, Christine Keiko; Rezende, Mirabel Cerqueira (Associação Brasileira de Polímeros, 2014)
In this work, polyarylacetylene (PAA) prepolymer obtained from 1,4-diethynylbenzene was evaluated as polymeric precursor of monolithic vitreous carbon (MVC). The monomer 1,4-diethynylbenzene was synthesized and the PAA prepolymer was prepared with 13, 16 and 19 wt % of nickel catalyst. The best percentage of nickel catalyst considered was 13 wt %, due to the lower molecular weight and polydispersity index and higher carbon yield. The traditional production of MVC is obtained from phenolic and poly(furfuryl alcohol) resins, which require many hours to pyrolyze due to the large quantity of gases generated. Furthermore, the porosity is hard to control using these conventional resins. Polyarylacetylene releases little volatiles due to the polyaddition reaction and the aromatic rings in PAA chain also provide a high thermal stability, therefore the heat treatment could be faster without cracking the carbon material. This would also lower the cost of fabrication of MVC, in addition to the low porosity observed, making this polymer a good matrix for MVC.
Keywords: Polyarylacetylene; 1,4-diethynylbenzene; Monolithic vitreous carbon; Porosity